2018
DOI: 10.1108/ijpsm-12-2016-0204
|View full text |Cite
|
Sign up to set email alerts
|

Municipal reaction to functional rescaling in Italy

Abstract: Purpose The purpose of this paper is to discuss the municipal reaction to a recent rescaling policy in Italy that, since 2010, require to small municipalities to jointly manage their basic tasks (compulsory joint management – CJM) through intermunicipal forms of cooperation. The paper will investigate: how many small municipalities did effectively join their basic tasks; which forms of cooperation did they choose to perform these tasks; and which kind of reaction municipalities enacted toward the national prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Against the background of the analytical framework described earlier, the contribution by Silvia Bolgherini et al (2018) touches on factors relating to intergovernmental relations, the degree of local autonomy, the extent of reforms, and cooperation between municipalities.…”
Section: Current Topics/trends In Local Service Delivery and Discussion Of Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Against the background of the analytical framework described earlier, the contribution by Silvia Bolgherini et al (2018) touches on factors relating to intergovernmental relations, the degree of local autonomy, the extent of reforms, and cooperation between municipalities.…”
Section: Current Topics/trends In Local Service Delivery and Discussion Of Contributionsmentioning
confidence: 99%
“…A rescaling policy recently introduced in Italy obliges small municipalities to manage basic tasks jointly in a form of IMC known as compulsory joint management (CJM). In their article, Bolgherini et al (2018) examined how small municipalities reacted to this policy, the extent to which they were effective in managing their joint functions together, the type of cooperation they adopted, and whether local governments resisted the reforms introduced. Quantitative data from official sources as well as qualitative data, generated by a semi-structured questionnaire, were analyzed and it was found that, in general, Italian local governments, complied poorly with the CJM requirements.…”
Section: Compulsory or Voluntary Local Government Reformsmentioning
confidence: 99%
“…However, this was enacted in each region with different timings, strategies, and designs (OPn.10). The Compulsory joint management (CJM) for municipalitiesintroduced in 2010 as OP, then reinforced by the Delrio Law and then definitely canceled in 2019 by the Constitutional Court (Bolgherini et al, 2018a) as SP (n.2)is an example of the uncertainty that followed. Overall, in the legal dimension, the prevalence of SPs (seven out of 11) is higher than that of the oblique ones (only three).…”
Section: Legalmentioning
confidence: 99%